Effect of COVID-19 vaccination on the outcome of in vitro fertilization: A systematic review and meta-analysis - Zhang, Linyu; Sun, Xinrui; Wang, Ruohan; Ma, Fang (Frontiers in Public Health, 2023)
Abstract Background: Universal COVID-19 vaccination programs are now recommended in several countries and represent the most effective preventive measure against COVID-19. However, some reports suggest that vaccination may cause infertility or have adverse effects on pregnancy. Conflicting reports have led to vaccine hesitancy in women planning pregnancy. Purpose: To determine whether vaccination against COVID-19 affects in vitro fertilization (IVF) outcomes, we conducted a meta-analysis. Method: A systematic search was conducted using PubMed, Embase, MEDLINE, and Web of Science databases for all published literature on COVID-19 vaccines and outcomes of IVF. International Prospective Register of Systematic Reviews registration was completed on September 13, 2022 (CRD42022359771). Results: We analyzed 20 studies totaling 18,877 individual cases undergoing IVF. COVID-19 vaccination had significant effect on clinical and ongoing pregnancy rate (risk ratio (RR): 0.97; 95% confidence interval (CI): 0.94–0.99; RR: 0.93; 95% CI: 0.87–0.99). These outcomes did not differ between vaccinated and unvaccinated individuals: biochemical pregnancy rate (RR: 0.95; 95% CI: 0.88–1.03), implantation rate (RR: 1.03; 95% CI: 0.92–1.15; P=0.61), the number of oocytes (mean difference (MD): 0.12; 95% CI: -0.65–0.88) and MⅡ/mature oocytes recovered (MD: 0.27; 95% CI: -0.36–0.90), blastocysts rate (MD: 0.01; 95% CI: -0.04, 0.06), and fertilization rate (MD: 1.08; 95% CI: -0.57, 2.73). Conclusion: Our findings suggest that vaccination against COVID-19 does not adversely affect the biochemical pregnancy rates; number of oocytes and MⅡ/mature oocytes obtained; implantation, blastocysts; and fertilization rates in women undergoing IVF treatment. Subgroup analysis showed that the mRNA vaccine had no statistical significance on all indexes (clinical, biochemical, or ongoing pregnancy rates; implantation, blastocysts, or fertilization rates; and the number of oocytes and MⅡ/mature oocytes). The findings of this meta-analysis are anticipated to increase the willingness of women planning IVF treatment to receive COVID-19 vaccination and provide evidence-based medical guidance for the development and implementation of guidelines.